Tinjauan Komprehensif Fiqh Muamalah : Pinjam Meminjam (‘Ariyah) dan Permasalahannya - Nuri, Muhammad Jain (Maliki Interdisciplinary Journal, 2026)
Borrowing and lending (’Ariyah) is a form of muamalah (transaction) that reflects the social values and sincerity of Islamic teachings. This contract occurs when someone lends an item that is not used up, such as a vehicle, household appliances, or clothing, with the aim of providing a benefit without compensation. The purpose of this study is to understand the basic concept of ’Ariyah, examine its legal basis in the Qur’an and Hadith, and analyze the problems that arise in its practice in modern society. This study uses a qualitative method with a descriptive-analytical approach based on classical fiqh literature and positive legal sources. The results show that ’Ariyah plays an important role in strengthening social solidarity, but often gives rise to problems such as damage to goods, late returns, and misuse of borrowed goods. Islam provides solutions by emphasizing clarity of the contract, the responsibility of the borrower, and the principle of justice in every transaction. Therefore, a correct understanding of the law of ’Ariyah needs to be strengthened so that this practice of mutual assistance remains in accordance with sharia values and avoids disputes